KEPRIBADIAN INTROVERT DALAM KEMAMPUAN BERSOSIALISASI PADA MAHASISWA - Muhammad Farel Saputra; Emilia Susanti; Selvi Salsabila; Devina Valeria Santani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This article discusses the influence of introverted personality on students’ socialization skills. Using a literature study method, this research explores the challenges faced by students with introverted personalities in social interactions within the academic environment. Introverted personality, characterized by a tendency to avoid crowds and focus more on oneself, can negatively impact social skills. The analysis results show that introverted students often face difficulties in socializing, lack confidence, and experience social anxiety. Although there are some findings indicating that introversion can contribute positively to deeper relationships, the dominant negative influence on socialization skills remains a strong theme. Therefore, this research suggests the need for a more supportive approach for introverted students to overcome social barriers and develop better interaction skills.